CONSULTATION AS A PROCESS OF KNOWLEDGE TRANSFER: MANAGEMENT TRAINING AND DECISION-MAKING IN SMALL BUSINESSES - Rizzo Rocha, Rafael (Journal of Interdisciplinary Debates, 2026)
The present study carries out a systematic review of the literature on the role performed by business consultancy as a mechanism for transferring knowledge focused on management training and decision-making processes in small and medium-sized enterprises (SMEs). The investigation, based on scientific publications from the period 2021-2025, examines the processes through which consultancy enables the acquisition and application of knowledge of a tacit and explicit nature, exerting influence on the development of managerial skills and improvement of decision making strategic. The research highlights the centrality of absorptive capacity (ACAP) as fundamental theoretical construct for understanding how SMEs internalize and explore knowledge from external sources, fostering innovation and organizational competitiveness. The review findings indicate that the consultancy, associated with transformational leadership and the incorporation of digital technologies, constitutes catalyzing element of organizational learning and performance improvement business in contexts marked by dynamism and resource constraints. The discussion articulates the themes of management training, decision making, learning organizational and digital transformation, outlining the challenges and opportunities that arise present to SMEs in the search for sustainable growth by taking advantage of external knowledge.